Cluster Assessment of the Innovation Dynamics in the Industry by Regions of Ukraine - Ishchuk, S. O.; Sozanskyy L. Yо.; Protseviat, O. S. (Statistics of Ukraine, 2025)
For the Ukrainian industry operating amidst structural transformations, war-related challenges, and resource limitations, innovations constitute not only a source of economic growth but also an important tool for renewal and modernization of the production capacities. The article’s objective is to determine the innovation dynamics in the industrial sector of the Ukrainian economy by region using cluster analysis. It is shown that the accelerated development of machine-building facilities in Ukraine has become a driver of innovation growth at industrial enterprises, which, in crucial areas, could exceed the prewar level. The innovation dynamics in Ukraine by region was assessed by a constructed set of four relative indicators measuring: the share of innovating enterprises in the total industrial enterprises; the share of enterprises that introduced innovations in the total industrial enterprises; the share of innovative products in the total sales of industrial products; the share of innovation expenses in the total capital investment. The results of clustering allowed to outline five phases of the spatial transformation in the innovation segment of the industrial sector of the Ukrainian economy: the phase of pre-crisis differentiation (five clusters in 2020), the phase of covid-provoked crisis (three clusters in 2021), the phase of shock adaptation (four clusters in 2022), the phase of deepening crisis (four clusters in 2023), and the phase of structural reconfiguration (three clusters in 2024), which confirmed the existence of a considerable regional differentiation in the innovation activity scales in the industry. An innovation nucleus was identified, consisting of Vinnytsia, Zaporizhzhia, Lviv, Ternopil, and Kharkiv oblasts, which continually belonged to the clusters with a high innovation activity of industrial enterprises. However, the most balanced innovation-development pattern in the industrial sector in 2024 was demonstrated by Dnipropetrovsk, Kirovohrad, and Khmelnitsk oblasts, where a moderate innovation activity (combined 16.69% of the total innovation expenses in Ukraine in 2024) generated maximal investment returns in the form of innovative product sales (combined 46.04% of the total innovative product sales in Ukraine).